2015
DOI: 10.1016/j.spc.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain management enablers: Mixed methods research

Abstract: A B S T R A C TThis paper contributes to the literature on green supply chain management (GSCM) by arguing for the use of mixed methods for theory building. The literature has identified antecedents and enablers for the adoption of GSCM practices. Nevertheless, there is relatively little research on building robust methodological approaches and techniques that take into account the dynamic nature of green supply chains. To address this gap, the paper firstly reviews systematically the literature on GSCM enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(78 citation statements)
references
References 138 publications
(48 reference statements)
3
72
0
3
Order By: Relevance
“…Data primer yang dikumpulkan adalah indikator manajemen lingkungan berdasarkan sertifikasi ISO 1400 sedangkan data sekunder yang dikumpulkan adalah data sertifikasi ISO 14001 tahun 2018 dan data pengolahan limbah perusahaan. Teknik pengambilan data menggunakan metode purposive sampling (mengambil subjek berdasarkan tujuan dan pertimbangan tertentu; Dubey et al, 2015). Jumlah sampel pada penelitian adalah sepuluh pakar yang mengetahui tentang manajemen lingkungan perusahaan.…”
Section: Metode Penelitianunclassified
“…Data primer yang dikumpulkan adalah indikator manajemen lingkungan berdasarkan sertifikasi ISO 1400 sedangkan data sekunder yang dikumpulkan adalah data sertifikasi ISO 14001 tahun 2018 dan data pengolahan limbah perusahaan. Teknik pengambilan data menggunakan metode purposive sampling (mengambil subjek berdasarkan tujuan dan pertimbangan tertentu; Dubey et al, 2015). Jumlah sampel pada penelitian adalah sepuluh pakar yang mengetahui tentang manajemen lingkungan perusahaan.…”
Section: Metode Penelitianunclassified
“…In the last decade, green manufacturing or green supply chain concept has been growing dramatically among researchers, managers, environmentalists and others (Gunasekaran, Spalanzani 2012;Brockhaus et al 2013). This is a developing trend among those companies, which make a connection between general green practices and their corporate strategies (Gunasekaran, Gallear 2012;Sarkis et al 2011;Dubey et al 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Green providers also need to perform identified green characteristics. Supply chain strategies, structures, core competencies, supply chain processes, and information systems are key to determining qualified green providers [12,13,19,24,25,34]. From the viewpoint of green supplier development practices, Bai and Sarkis [25] grouped a set of 30 green provider characteristics into three major categories: (a) green knowledge transfer and communication; (b) investment and resource transfer; and (c) management and organizational practices.…”
Section: Eco-friendly Enterprise Conceptual Modelmentioning
confidence: 99%
“…These criteria are as follows: (a) developing environmentally friendly products; (b) implementing environmentally friendly internal operations; (c) gaining recognition for environmentally positive behaviors; (d) environmentally friendly purchasing; (e) environmental collaboration with customers; (f) encouraging suppliers to adopt more environmentally friendly behaviors; (g) interacting with customers to change product specifications; (h) reverse logistics; (i) ISO 14001 certification; and (j) waste minimization. A GSCM development literature review conducted by Dubey et al [34] reported five principal components encompassing 26 GSCM providers. These providers were: (a) top-management commitment; (b) institutional pressure; (c) supplier relationship management; (d) total quality management; and (e) green technology adoption.…”
Section: Eco-friendly Enterprise Conceptual Modelmentioning
confidence: 99%